2021
DOI: 10.3389/fspor.2021.695666
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Child Rights Principles and Practises in Mega Sport Event Planning

Abstract: Recently, there has been growing concern about the lack of intentionality of mega sport event (MSE) organisers in ensuring that child rights are adequately respected, protected and promoted before, during, and after the events take place. In the context of the summer Olympic Games, reported child rights infringements have been on the rise, both in relation to abuse in sport itself and the negative consequences associated with planning and delivering the Games. In response to reports of child rights infringemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Focusing on the Tokyo 2020 Olympic Games, Aina et al (2021) show that while the Japanese authorities signed up to international child rights conventions and embedded some child participation strategies in Games-related activity, there was little evidence that they had developed or implemented robust policies, principles or practices to respect, protect and promote child rights in Games planning. comments on the IOC's requirement for host cities to adhere to the United Nations Guiding Principles on Business and Human Rights.…”
Section: Organizational Actors Change and Human Rightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the Tokyo 2020 Olympic Games, Aina et al (2021) show that while the Japanese authorities signed up to international child rights conventions and embedded some child participation strategies in Games-related activity, there was little evidence that they had developed or implemented robust policies, principles or practices to respect, protect and promote child rights in Games planning. comments on the IOC's requirement for host cities to adhere to the United Nations Guiding Principles on Business and Human Rights.…”
Section: Organizational Actors Change and Human Rightsmentioning
confidence: 99%
“…Despite this, research examining issues of children's rights from the Tokyo 2020 Olympic Games found that there were no embedded child rights commitments in the bidding or planning documents, resulting in few measures to implement or report child rights abuses (Aina et al, 2021). to adhere to internationally recognized standards such as the UNCRPD.…”
Section: Host City Residents House Owners or Tenants And (Migrant) Wo...mentioning
confidence: 99%